2008
DOI: 10.1038/onc.2008.426
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation-induced colon tumorigenesis in mice deficient in the Mgmt and Msh6 proteins

Abstract: O6-methylguanine DNA methyltransferase (MGMT) suppresses mutations and cell death that result from alkylation damage. MGMT expression is lost by epigenetic silencing in a variety of human cancers including nearly half of sporadic colorectal cancers, suggesting that this loss maybe causal. Using mice with a targeted disruption of the Mgmt gene we tested whether Mgmt protects against azoxymethane (AOM) induced colonic aberrant crypt foci (ACF), against AOM and dextran sulfate sodium (DSS) induced colorectal aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
(40 reference statements)
1
35
0
Order By: Relevance
“…27 We hypothesized that the roles of APC associated with aging may be absent while DNA repair pathways associated with mucosal damage would be present in the DSS-induced acute colitis young rat model, because mutations or deficiencies in APC and MMR contribute significantly to the development of age-related or familial colonic neoplasia and sporadic or mucosal-damage-related neoplasia, respectively. 3,8,17 As expected, young rats failed to gain body weight and had loose stools after DSS treatment, resulting in significantly different growth curves (P < 0.01). Together with the histological changes associated with acute colitis, APC immunolocalization was evident in the surface epithelium and lamina propria at the end of the study.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…27 We hypothesized that the roles of APC associated with aging may be absent while DNA repair pathways associated with mucosal damage would be present in the DSS-induced acute colitis young rat model, because mutations or deficiencies in APC and MMR contribute significantly to the development of age-related or familial colonic neoplasia and sporadic or mucosal-damage-related neoplasia, respectively. 3,8,17 As expected, young rats failed to gain body weight and had loose stools after DSS treatment, resulting in significantly different growth curves (P < 0.01). Together with the histological changes associated with acute colitis, APC immunolocalization was evident in the surface epithelium and lamina propria at the end of the study.…”
Section: Discussionmentioning
confidence: 65%
“…MMR contributes to the development of both sporadic and mucosal-damage-related neoplasia. 8,[12][13][14][15][16][17][18] We were interested in the relationship between MMR and BER in preventing DNA damage against DSS-induced colitis in young rats because MYH, which is involved in BER, is also associated with the development of colorectal cancer, and its activity is modulated by MMR and APE1. 20,21 We found that APE1 and MSH2 levels increased significantly at DSS-3d and DSS-5d, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If O 6 MeG remains in one of the template strands the repair process will be repeated, creating a "futile repair loop". This loop will eventually result in toxic double-strand breaks leading to chromosomal aberrations, cell-cycle arrest or apoptosis (Bugni et al, 2009;Kaina et al, 2007;Kaina et al, 2010;Kondo et al, 2010). When both of these systems fail to repair, O 6 MeG results in point mutations that can possibly initiate the carcinogenic process.…”
Section: Direct Damage Reversal Repairmentioning
confidence: 99%
“…Depletion of MGMT by reducing MGMT activity or decreasing gene expression can occur using a specific inhibitor O 6 -benzylguanine (BG) or through epigenetic silencing, (Eker et al, 2009). Inhibition of MGMT with BG in rats increases azoxymethane (AOM)-induced colon tumors, and transgenic e x p r e s s i o n o f M G M T i n m i c e p r o t e c t s a g a i n s t A O M -i n d u c e d aberrant crypt foci (ACF) (Bugni et al, 2009;Wali et al, 1999).…”
Section: Direct Damage Reversal Repairmentioning
confidence: 99%